Distribution of baryonic and dark matter in spiral and irregular nearby galaxies - Korsaga, Marie (Department of Astronomy, 2019)
My PhD research is focused on the dark matter (DM) and luminous matter distribution in spiral and irregular galaxies. Studying this matter could clearly improve our knowledge on the formation and evolution of galaxies. While the overall description of the baryon content of galaxies is now well known, we will now use the kinematics to understand the distribution of DM, especially in the inner parts of galaxies. To do this, I study the distribution of the luminous and DM in nearby galaxies. The study consists of using the GHASP (Gassendi HAlpha survey of SPirals) sample which allows me to investigate the distribution of the DM halos in the inner regions of galaxies, by connecting the kinematical data from the optical observations to the photometry data available in the literature. After summarizing the global properties of the luminous and DM of galaxies, I present the instruments based on the FabryPerot interferomter used to observe the GHASP survey. I also present the different photometry (infrared and optical bands) data, and models used to determine the distribution of luminous and DM inside galaxies. In chapter 2, we present the kinematical data and the infrared photometry data available in the literature used to construct galaxy mass models. For the kinematical data, we use rotation curves from the GHASP survey. For the photometry data, we use the luminosity profile of the mid-infrared W1 and W2 (3.4 and 4.6 µm) of WISE (Wide-field Infrared Survey Explorer), which probes the emission from the old stellar population. The radial profile is decomposed if necessary to multiple components (bulge, disc, bar, spiral arm, ect.). Combining the optical kinematical data with the infrared photometry data allows us to determine the mass distribution of the sample of 121 galaxies covering morphological types from S0 to Irr, and therefore to understand how the DM halo is distributed in early type spiral compared to late type spiral and irregular galaxies. We use two main models to describe the shape of the DM halos in galaxies: the pseudo-isothermal core density profile and the Navarro-Frenk-White cuspy density profile. We allow the mass-to-light ratios of the disc and if necessary the bulge to vary and we keep them fixed by the colour (W1- W2). We also explore the maximum disc for the pseudo-isothermal model. We find that the two profiles describe well the rotations curves while the pseudo-isothermal model gives better results. In order, to understand how the DM is distributed, we study relations between the parameters of the DM and the luminosity of galaxies. We find that the relations between the DM halo parameters and the luminosity of galaxies depend on the morphological types (presence of bulge or not in galaxies). In chapter 3, we present the mass distribution of 100 early and late type spiral and irregular galaxies by combining the kinematical data (Hα rotation curves) with the optical Rc band photometry data available in the literature. We use the same methods and descriptions given in Chapter 2. The mass-to light ratios are now fixed using the (B - V) colour. We compare the results obtained using the optical Rc band photometry to the W1 band photometry. We find similar results on the DM halo parameters but the values are higher for the mass-to-light ratios in the Rc band than in the W1. However the dispersion in the model parameters is smaller and because stellar masses are better defined, the infrared photometry should be preferred, when possible, to the optical band. The Hi rotation curves are crucial in studying the distribution of the DM in the inner and outer regions of galaxies. In chapter 4, we first construct the mass distribution of 31 galaxies using the Hα rotation curves and mid-IR photometry data used in chapter 2 with the addition of the contribution from the Hi gas component. Secondly, the mass distribution is determined with the same photometry and gas component but using hybrid (Hα and Hi) extended rotation curves. Lastly, the mass distribution is constructed using Hi kinematical data. The main goal is to understand how the luminous and DM parameters may vary when using the different kinematical data. We use the same models to construct the mass models and the fitting procedures as described in chapter 2. We find that the relation between the parameters varies from one dataset to the other.